Intermittent Fasting Alleviates the Increase of Lipoprotein Lipase Expression in Brain of a Mouse Model of Alzheimer's Disease: Possibly Mediated by β-hydroxybutyrate - Zhang, Jingzhu; Li, Xinhui; Ren, Yahao; Zhao, Yue; Xing, Aiping; Jiang, Congmin; Chen, Yanqiu; An, Li (Frontiers in Cellular Neuroscience, 2018)
Intermittent fasting has been demonstrated to protect against Alzheimer’s disease (AD), however, the mechanism is unclear. Histone acetylation and lipoprotein lipase (LPL) are involved in AD progression. Importantly, LPL has been documented to be regulated by histone deacetylases (HDACs) inhibitors (increase histone acetylation level) in adipocyte and mesenchymal stem cells, or by fasting in adipose and muscle tissues. In brain, however, whether histone acetylation or fasting regulates LPL expression is unknown. This study was designed to demonstrate intermittent fasting may protect against AD through increasing β-hydroxybutyrate, a HDACs inhibitor, to regulate LPL. We also investigated microRNA-29a expression associating with regulation of LPL and histone acetylation. The results showed LPL mRNA expression was increased and microRNA-29a expression was decreased in the cerebral cortex of AD model mice (APP/PS1), which were alleviated by intermittent fasting. No significant differences were found in the total expression of LPL protein (brain-derived and located in capillary endothelial cells from peripheral tissues) in the cerebral cortex of APP/PS1 mice. Further study indicated that LPL located in capillary endothelial cells was decreased in the cerebral cortex of APP/PS1 mice, which was alleviated by intermittent fasting. LPL and microRNA-29a expression were separately increased and down-regulated in 2 μM Aβ25-35-exposed SH-SY5Y cells, but respectively decreased and up-regulated in 10 μM Aβ25-35-exposed cells, which were all reversed by β-hydroxybutyrate. The increase of HDAC2/3 expression and the decrease of acetylated H3K9 and H4K12 levels were alleviated in APP/PS1 mice by intermittent fasting treatment, as well in 2 or 10 μM Aβ25-35-exposed cells by β-hydroxybutyrate treatment. These findings above suggested the results from APP/PS1 mice were consistent with those from cells treated with 2 μM Aβ25-35. Interestingly, LPL expression was reduced (0.2-folds) and microRNA-29a expression was up-regulated (1.7-folds) in HDAC2-silenced cells, but respectively increased (1.3-folds) and down-regulated (0.8-folds) in HDAC3-silenced cells. Furthermore, LPL expression was decreased in cells treated with microRNA-29a mimic and increased with inhibitor treatment. In conclusion, intermittent fasting inhibits the increase of brain-derived LPL expression in APP/PS1 mice partly through β-hydroxybutyrate-mediated down-regulation of microRNA-29a expression. HDAC2/3 may be implicated in the effect of β-hydroxybutyrate on microRNA-29a expression.